INTRODUCTION TO ANDREAS KABLITZ’S RENAISSANCE – REBIRTH: SOME REMARKS ABOUT THE HUMANISTIC INTERPRETATION OF HISTORY - Behler, Ernst (Surfaces, 2001)
In the context of the Third International Conference on Humanistic Discourse, this text introduces Andreas Kablitz’s "Renaissance-Rebirth: Some Remarks about the Humanistic Interpretation of History" and reports on the central concerns that emerged in its discussion.